Implementation of First Aid Education: Ready, Smart, and Responsive in Building a Safety Culture in Students of SMPN 3 Balikpapan - Christian Adinata; Salsa Ramadhani; Olivia Dwi Kuswa; Anindita Syafira; Imelda Nur Aisyah; M. Rafly Pratama Hidayah; Retnowaty Retnowaty; Besse Intan Permata Sari; Prita Indriawati; Wahyuni Wahyuni (Indo Publishing, 2026)
This article aims to evaluate the implementation of first aid education based on the principles of Being Prepared, Smart, and Responsive in fostering a safety culture among students at SMP N 3 Balikpapan. This article was motivated by an increase in minor injuries within the school environment, which highlights the need for students to possess basic skills in providing initial responses during emergency situations. The educational activities were delivered through interactive methods, including presentations, discussions, and question-and-answer sessions. The results indicate that the first aid education program enhanced students’understanding of emergency procedures, including Cardiopulmonary Resuscitation (CPR), bleeding control, injury management, poisoning response, burn care, and animal bite treatment. Students also demonstrated positive behavioral changes, such as improved preparedness, greater concern for peers, and accuracy in responding during emergency simulations. This article concludes that first aid education significantly contributes to strengthening the safety culture in schools and is recommended for continuous implementation as part of an ongoing health education program.